Various Analytical Methods for Estimation of Potassium Sorbate in Food Products: A Review - Salwan, Sushant; Passi, Indu; Kumar, Bhupinder (Current Analytical Chemistry, 2022)
Food preservatives are used to keep bacteria, moulds, fungus, and yeast from spoiling food. Food additives are subject to strict rules (particularly in the European Union - EU), which consider the food to which they can be applied, maximum permissible quantities, chemical characterization, and purity. Sorbic acid, mainly potassium sorbate, is primarily utilised in a variety of commercially available foods. Various analytical strategies for an asynchronous and simultaneous estimation of potassium sorbate have been reported along with other preservatives in marketed formulations or food products. The Square-wave voltammetry using a cathodically prepared boron-doped diamond electrode, quick UHPLCfluorescent method, UV spectrophotometry, UHPLC-UV analysis, RP-HPLC, and mass spectrometry are some of the analytical techniques used. We have compiled various analytical methods to detect potassium sorbate with various other preservatives simultaneously or alone in marketed formulation. The authors feel that the studies summarised in this report will allow readers to choose the most acceptable and appropriate method for analysing this preservative.
Keywords: RP-HPLC